A Mobile-Programmable Smart Mirror for Ambient IoT Environments - Ghazal, Mohammed; Al Hadithy, Tara; Al Khalil, Yasmina; Akmal, Muhammad; Hajjdiab, Hassan (2017 5th International Conference on Future Internet of Things and Cloud Workshops (FiCloudW), 2017)
The purpose of this paper is to present a smart interactive mirror interface. In this paper, we describe the design and development of a futuristic mirror that offers simplified and customisable services to the home environment. On a par with the recent advances in the Internet of Things standards and applications, the mirror is designed to enable residents to control the household smart appliances and access personalised services; ensuring convenience in accessing these services with the slightest possible user intervention. The multipurpose user-friendly functionalities of the proposed mirror interface provide users with the versatility needed for better management and integration of daily tasks. A service oriented approach is adopted in the architecture of the proposed system. It consists mainly of two mobile applications devoted to the customisation of user profiles, which are displayed on the smart mirror interface once successfully paired. Moreover, in the proposed system, emphasis is particularly given to the user profile personalisation, as well as planned system interactivity and adaptability. Hence, the proposed system is set apart from others for its ease of use as well as its provision of various customised information services for user profile generation.